2023
DOI: 10.3389/fgwh.2023.1112392
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mifepristone plus misoprostol with misoprostol alone for first trimester medical abortion: A systematic review and meta-analysis

Abstract: ObjectiveTo compare mifepristone plus a misoprostol-combined regimen with misoprostol alone in the medical abortion of first trimester pregnancy.MethodsAn internet-based search of available literature was performed using text words contained in titles and abstracts. PubMed/Medline, Cochrane CENTRAL, EMBASE, and Google scholar were used to locate English-based articles published until December 2021. Studies fulfilling the inclusion criteria were selected, appraised, and assessed for methodological quality. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Some experts launched studies to evaluate possible combination with misoprostol and other drugs to induce complete uterine evacuation. Shimels et al conducted a systematic review and meta-analysis to compare the relative e ciency in treating incomplete miscarriage by misoprostol plus mifepristone or by misoprostol alone, which demonstrated that combination of misoprostol and mifepristone achieved better outcomes [21] . Another study focused on the relative e cacy of misoprostol in treating second trimester abortion in terms of regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Some experts launched studies to evaluate possible combination with misoprostol and other drugs to induce complete uterine evacuation. Shimels et al conducted a systematic review and meta-analysis to compare the relative e ciency in treating incomplete miscarriage by misoprostol plus mifepristone or by misoprostol alone, which demonstrated that combination of misoprostol and mifepristone achieved better outcomes [21] . Another study focused on the relative e cacy of misoprostol in treating second trimester abortion in terms of regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a new treatment arose, the combination of Mifepristone-Misoprostol regime, which was shown to be superior to the Misoprostol only regime [17].…”
Section: Introductionmentioning
confidence: 99%